Species diversity and daily infestation patterns of Haematophagus flies in cattle farms at Tanah Bumbu District, South Kalimantan Province, Indonesia - BUDI HAIRANI; UPIK KESUMAWATI HADI; SUPRIYONO SUPRIYONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hairani B, Hadi UK, Supriyono. 2023. Species diversity and daily infestation patterns of Haematophagus flies in cattle farms at Tanah Bumbu District, South Kalimantan Province, Indonesia. Biodiversitas 24: 2995-3003. Blood-sucking flies act as livestock pests and vectors of zoonotic diseases. This study aims to know the species diversity of blood-sucking flies, relative abundance, frequency, and dominance of species and their correlation to weather parameters on beef cattle farms with three different ecosystems in the Tanah Bumbu District, South Kalimantan, Indonesia. The research was conducted from August to October 2022 on 6 beef cattle farms in Tanah Bumbu District with different types of ecosystems, namely forest, non-forest, and coastal areas. The flies was collected by using sweep nets, NZI traps. and Vavoua traps. Blood meal activity was measured by counting flies infestation on the cow's body. The results showed that there were 11 species of blood-sucking flies, i.e., Stomoxys calcitrans Linnaeus 1758, S. sitiens Rondani 1873, S. indicus Picard 1908, S. bengalensis Picard 1908, Haematobia exigua Meijere 1903, Therioplectes sp., Chrysops fixissimus Walker 1856, Tabanus optatus Walker 1856, T. striatus Fabricius 1787, T. rubidus Wiedemann 1821, and Hippobosca sp. The S. calcitrans population appears to be dominat in each type of ecosystem. The peak of blood-sucking fly infestations on the body of beef cattle in each ecosystem occurred at 10AM-2PM. In addition, the environmental temperature and humidity were significantly correlated to fluctuations in blood-sucking fly infestations in each ecosystem, and the light intensity was significantly correlated to the population of H. exigua in coastal ecosystems, while the wind velocity was not significantly correlated to all species in all ecosystems.